2022
DOI: 10.1021/acsami.2c03270
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Driven α-β Phase Transformation and Enhanced Electronic Property of 2H α-In2Se3

Abstract: In recent years, thin layered indium selenide (In2Se3) has attracted rapidly increasing attention due to its fascinating properties and promising applications. Here, we report the temperature-driven α-β phase transformation and the enhanced electronic property of 2H α-In2Se3. We find that 2H α-In2Se3 transforms to β-In2Se3 when it is heated to a high temperature, and the transformation temperature increases from 550 to 650 K with the thickness decreasing from 67 to 17 nm. Additionally, annealing the sample bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…To investigate the thermal stability for sulfurized and defective In 2 Se 3 , we further performed AIMD simulations, as shown in Figure g. It is reported that α-In 2 Se 3 -based ferroelectric devices present ultrahigh and thickness-dependent curie temperatures from ∼473 to ∼700 K. ,, On the basis of those findings, AIMD simulations for monolayer In 2 Se 3 are carried out at an elevated temperature of around 550 K. The simulation time of 10 ps is long enough to monitor the structure evolutions and evaluate their thermal stability. The corresponding snapshots (Figure g,h) are atomic structures for sulfurized and defective In 2 Se 3 enduring AIMD simulation, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the thermal stability for sulfurized and defective In 2 Se 3 , we further performed AIMD simulations, as shown in Figure g. It is reported that α-In 2 Se 3 -based ferroelectric devices present ultrahigh and thickness-dependent curie temperatures from ∼473 to ∼700 K. ,, On the basis of those findings, AIMD simulations for monolayer In 2 Se 3 are carried out at an elevated temperature of around 550 K. The simulation time of 10 ps is long enough to monitor the structure evolutions and evaluate their thermal stability. The corresponding snapshots (Figure g,h) are atomic structures for sulfurized and defective In 2 Se 3 enduring AIMD simulation, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman spectrum (see Figure 2h) acquired from the central area of pristine In 2 Se 3 single crystal shows several characteristic peaks centered at 83.5, 105.5, 153.8, 168.6, 183.8, and 202.5 cm −1 , demonstrating the synthesis of α-In 2 Se 3 . 36,38 Among them, the prominent peaks located at 83.5, 105.5, 183.8, and 202.5 cm −1 are assigned to the E, A 1 (LO + TO), A 1 (TO), and A 1 (LO) phonon modes of α-In 2 Se 3 , respectively. 39,40 The EDS spectra (see Figure 2i) acquired from corresponding pristine and sulfurized samples show that the characteristic peak of elemental selenium appears, while that of elemental sulfur vanishes after sulfurization treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Successive mechanical exfoliation of the same flakes results in a few-layer sample of In 2 Se 3 , which can then be transferred onto a substrate for analysis. Many reports that study the properties of a single phase of In 2 Se 3 utilize this method, given its reliability and ease of preparation. …”
Section: Preparation Methods For Polymorphs and Polytypesmentioning
confidence: 99%
“…Multilayer In 2 Se 3 has been employed as a channel material for semiconductor field effect transistors (FETs) in a multitude of studies in recent years. Its coupled in-plane and out-of-plane dipole locking mechanism has enabled versatile device design, ranging from its use as the primary channel component to be utilized as a wrapping material for a semiconductor channel. ,,, …”
Section: Properties and Applications Of In2se3mentioning
confidence: 99%
“…Ferroelectric materials have received intensive attention in the past decades due to their potential applications in electronic devices such as nonvolatile memory. The growing demand of ultrahigh density storage requires a smaller size for functional domains as well as ultrathin thickness. , However, the traditional ferroelectric oxides on the nanoscale have been limited by the long-standing issue of critical thickness, below which the ferroelectric polarization would disappear. ,, The recently discovered two-dimensional (2D) ferroelectric materials shine a light on the development of ultra-high-density memory as the nanoscale 2D ferroelectrics can retain a sizable polarization with extraodingary electronic properties. With the inherent stable, layered structure and clean surface, 2D van der Waals (vdW) materials are suitable candidates to study ferroelectricity at the limitation of the atomic layer. , Among the various 2D ferroelectric vdW materials demonstrated in experiments, ,, the 2D vdW material In 2 Se 3 was reported to maintain spontaneous polarization even at monolayer thickness. ,,, The monolayer In 2 Se 3 has quintuple atomic layers in the sequence of Se–In–Se–In–Se, and the spontaneous polarization originates from the atomic displacement of the middle Se layer. The unique atomic structure leads to an intrinsic coupling of the in-plane (IP) and out-of-plane (OOP) polarizations, , resulting in multifunctional applications such as electromechanical transducer and artificial intelligence synapse devices. ,, The excellent optical and ferroelectric properties of In 2 Se 3 also make it promising for applications in optoelectronics, photovoltaics, and information processing. ,,, Given its wide applications, great efforts have been devoted to achieve the synthesis of large-scale 2D In 2 Se 3 with a uniform thickness.…”
mentioning
confidence: 99%